Ocimum gratissimum L. leaf flavonoid-rich extracts reduced the expression of p53 and VCAM in streptozotocin-induced cardiomyopathy rats - Basiru Olaitan Ajiboye; Courage Dele Famusiwa; John Adeolu Falode; Adetutu Omolola Ojelabi; Atimone Nofisat Mistura; Demilade Olakunle Ogunbiyi; Temitope Olawale Jeje; Olapade Samuel Akinlolu; Oluwatosin Olalekan Ogedengbe; Oluwafemi Adeleke Ojo (Elsevier, 2024)
Background: This study aimed to investigate the potential cardioprotective effects of flavonoid-rich extracts from Ocimum gratissimum leaves in a streptozotocin-induced diabetic rat model by assessing redox stress biomarkers, ATPase activities, gene expression levels, enzyme activities, and histopathological changes. Methods: Diabetic rats were administered low (LDOGFL) and high (HDOGFL) doses of O. gratissimum leaf flavonoid-rich extracts, metformin (MET), or served as diabetic (DC) and normal (NC) controls for twenty-one days. Various cardiac parameters were evaluated, including redox stress biomarkers, ATPase activities, relative gene expression of p53 and VCAM, phosphatase activities, transaminase activities, serum creatine kinase-MB (CKMB) activities, cardiac troponin levels, and natriuretic peptide levels. Additionally, heart histoarchitecture was also examined using hematoxylin and eosin (H&E) staining. Results: Flavonoid-rich extracts of O. gratissimum significantly (p < 0.05) mitigated redox stress by decreasing malondialdehyde (MDA) levels and increasing reduced glutathione (GSH), glutathione-S-transferase (GST), catalase (CAT), glutathione peroxidase (GPx), and superoxide dismutase (SOD) activities in diabetic treated rats. The extracts also notably (p < 0.05) improved ATPase activities and significantly (p < 0.05) modulated the relative gene expression of p53 and VCAM in diabetic treated rats. Furthermore, diabetic rat administered flavonoid-rich extracts markedly (p < 0.05) attenuated phosphatase activities, transaminase activities, CKMB activities, cardiac troponin levels, and natriuretic peptide levels. Histopathological examination of the diabetic rats revealed improved cardiac histoarchitecture in extract-treated groups compared to diabetic controls. Conclusion: These findings suggest that O. gratissimum leaf flavonoid-rich extracts confer cardioprotective effects in STZ-induced diabetic rats by ameliorating redox imbalance, modulating gene expression, regulating enzyme activities, and preserving cardiac histoarchitecture. These results highlight the potential therapeutic application of O. gratissimum flavonoids in managing diabetes-induced cardiomyopathy.